Permafrost Base Degradation: Characteristics and Unknown Thread With Specific Example From Hornsund, Svalbard - Dobiński, Wojciech; Kasprzak, Marek (Frontiers in Earth Science, 2022)
Permafrost degradation is one of the most pressing issues in the modern cryosphere related to climate change. Most attention is paid to the degradation of the top of the active permafrost associated with contemporary climate. This is the most popular issue because in the subsurface part of it there is usually the greatest accumulation of ground ice in direct relation to the changes taking place. The melting of ground ice is the cause of the greatest changes related to subsidence and other mass-wasting processes. The degradation of the subsurface permafrost layer is also responsible for the increased emission of CO2 and methane. However, this is not a fully comprehensive look at the issue of permafrost degradation, because depending on its thickness, changes in its thermal properties may occur more or less intensively throughout its entire profile, also reaching the base of permafrost. These changes can degrade permafrost throughout its profile. The article presents the basic principles of permafrost degradation in its overall approach. Both the melting of the ground ice and the thermal degradation of permafrost, as manifested in an increase in its temperature in part or all of the permafrost profile, are discussed. However, special attention is paid to the degradation characteristics from the permafrost base. In the case of moderately thick and warm permafrost in the zone of its sporadic and discontinuous occurrence, this type of degradation may particularly contribute to its disappearance, and surficial consequences of such degradation may be more serious than we expect on the basis of available research and data now. A special case of such degradation is the permafrost located in the coastal zone in the vicinity of the Hornsund Spitsbergen, where a multidirectional thermal impact is noted, also causing similar degradation of permafrost: from the top, side and bottom. Especially the degradation of permafrost from the permafrost base upwards is an entirely new issue in considering the evolution of permafrost due to climate change. Due to the difficulties in its detection, this process may contribute to the threats that are difficult to estimate in the areas of discontinuous and sporadic permafrost.